(3GdahGFO GdMGFQjI GdCUhdjI GdChdI GdYJjbI GdbOjeIs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3GHf eMeO GdJfcGHGfj GdMGFQjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3EPG XgQ ef aYd GdTGQY Chdg GdeWdb Cf TjFG LRA dYHGOI aGdCUd chfg Qcf JHWd GdYHGOI eJHQcI YeOG SghG Ch LgdG EdG Cf jKHJ NdGag HCfg dG jVQ aj HYV GdUhQ hcPG JHWd HRjGOJg (B...s
(3BNQgG (B:s
.. (3ajUM Cf jUjQ GdCUd (B... (3eSJOd eY Cf GdCOdI GdabgjI QHeG jchf HYVgG ZjQ hGa dLeY GdeWdhH (B.. (3dGHO ef KHhJ GdMce HGdCOdI cja cGf Je GdcJGH (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3GdPQjYI (B16\1536s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs